Study on the mechanical properties of layered gradient structure PBT-based flame retardant composite materials - Peng Cui; Lei Niu; Shibo Ren (Materials Research Express)
Polybutylene Terephthalate (PBT) was widely used for its excellent mechanical properties, low moisture absorption, and good chemical corrosion resistance. To enhance the flame retardancy of PBT while addressing the decrease in mechanical properties caused by flame retardants, this study employed brominated polystyrene (BPS) as the flame retardant and modified nano-antimony trioxide (nano-Sb _2 O _3 ) as a synergistic flame retardant. These were added to PBT, and a gradient distribution of nano-Sb _2 O _3 was achieved through lamination hot-pressing technology. The effects of this gradient distribution on the flame retardancy and mechanical properties of the composite materials were investigated. The results show that the modifiers Cetyltrimethylammonium bromide (CTAB) and γ -Glycidoxypropyltrimethoxysilane (KH560) successfully graft onto the nano-Sb _2 O _3 surface, enhancing its compatibility with the matrix material. Compared to the homogeneous composite materials, the gradient composites exhibit an increased Limiting Oxygen Index (LOI), with the most significant improvement seen in the composite (G828) that has a 6 wt% difference in concentration between the outer and inner layers, increasing the LOI by 6%. Additionally, as the concentration of nano-Sb _2 O _3 on the surface of the composite material increases, so does the amount of char residue. Compared to homogeneous composites, the gradient composites show significant improvements in mechanical properties, with G828 exhibiting increases of 19.7% in tensile strength, 37.1% in bending strength, and 103% in impact strength, demonstrating the significant effect of the gradient distribution in enhancing both flame retardancy and mechanical properties of the composite material.